DAMPAK RISIKO MAKRO DAN MIKRO INVESTASI SUB SEKTOR PERKEBUNAN LAHAN BASAH - Sadikin, Ali; Dahniar, Dahniar; Dalimunthe, Fahmi Roy; Rusniati, Rusniati; Rachman, M. Yudi (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2024)
This research is motivated by the problem that stock returns are influenced by micro and macro investment risk factors of an investment portopolio. The purpose of this study is to determine and analyze the impact of micro and macro investment risk factors from an investment portfolio in the wetland plantation sub-sector listed on the IDX for the period 2021-2023. The independent variables used are BI interest rates, Inflation and Financial Risk on Stock Returns as the dependent variable.Â Â This study uses a quantitative approach with a population of 24 companies, a sample size of 21 companies using a purposive sample method. The analysis method applied is Descriptive Statistical analysis, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, Multiple Linear Regression Test, T Test, and Coefficient of Determination. The result of this study is that all classical assumptions pass the test. In the T test (partial test) on hypothesis H: 1 BI interest rate has a significant effect on stock returns in the wetland plantation sub-sector, while H: 2 and H: 3 Inflation and Financial Risk have no effect on Stock Returns in the Wetland Plantation sub-sector